Cell Fate and Differentiation of Bone Marrow Mesenchymal Stem Cells - Kokabu, Shoichiro (Stem Cells Int, 2016)
Osteoblasts and bone marrow adipocytes originate from bone marrow mesenchymal stem cells (BMMSCs) and there appears to be a reciprocal relationship between adipogenesis and osteoblastogenesis. Alterations in the balance between adipogenesis and osteoblastogenesis in BMMSCs wherein adipogenesis is increased relative to osteoblastogenesis are associated with decreased bone quality and quantity. Several proteins have been reported to regulate this reciprocal relationship but the exact nature of the signals regulating the balance between osteoblast and adipocyte formation within the bone marrow space remains to be determined. In this review, we focus on the role of Transducin-Like Enhancer of Split 3 (TLE3), which was recently reported to regulate the balance between osteoblast and adipocyte formation from BMMSCs. We also discuss evidence implicating canonical Wnt signalling, which plays important roles in both adipogenesis and osteoblastogenesis, in regulating TLE3 expression. Currently, there is demand for new effective therapies that target the stimulation of osteoblast differentiation to enhance bone formation. We speculate that reducing TLE3 expression or activity in BMMSCs could be a useful approach towards increasing osteoblast numbers and reducing adipogenesis in the bone marrow environment.